House of Odysseus - North, Claire (North, Claire. Songs of Penelope, 2023)
"On the isle of Ithaca, queen Penelope maintains a delicate balance of power. Many years ago, her husband Odysseus sailed to war with Troy and never came home. In his absence, Penelope uses all her cunning to keep the peace--a peace that is shattered by the return of Orestes, King of Mycenae, and his sister Elektra. Orestes' hands are stained with his mother's blood. Not so long ago, the son of Agamemnon took Queen Clytemnestra's life on Ithaca's sands. Now, wracked with guilt, he is slowly losing his mind. But a king cannot be seen to be weak, and Elektra has brought him to Ithaca to keep him safe from the ambitious men of Mycenae. Penelope knows destruction will follow in his wake as surely as the furies circle him. His uncle Menelaus, the battle-hungry king of Sparta, longs for Orestes' throne--and if he can seize it, no one will be safe from his violent whims. Trapped between two mad kings, Penelope fights to keep her home from being crushed by a war that stretches from Mycenae and Sparta to the summit of Mount Olympus itself. Her only allies are Elektra, desperate to protect her brother, and Helen of Troy, Menelaus' wife. And watching over them all is the goddess Aphrodite, who has plans of her own. Each woman has a secret. And their secrets will shape the world"--